Dry bloodstain detection on various black fabric using forensic light sources - Mohamed, Omar Osman (2022)
Blood is one of the most frequent and crucial biological methods used to identify and characterise criminals and regularly used to establishing a link between the offender, the victim, and the crime. Blood and bloodstain evidence in the form of fluids or stains found at the scene of a crime in large quantities or in tiny amounts. This study investigates dried blood stain on the dark fabric of cotton, polyester, and mixed (cotton/polyester). This study looked into using Crime lite to photograph bloodstains to provide an alternative noninvasive tool. This study examined whether blood always absorbed light in the 300nm to 900nm range and the best wavelength for observing blood on black fabrics. It also investigated whether fabric type affected the ability to view blood on fabrics, if washing and drying the fabric affected the use of forensic light source (FLS) and if so, to what extent. Blood drops were deposited on three fabrics were photographed in the Crime-lite 2s FLS kit (Foster and Freeman) with and without a filter under 400-700nm (white light), 350nm- 380nm (UV), 400nm-430nm (Violet), 420nm-470nm (Blue), and 445nm-510nm (Blue green). The observation was optimized using positive control samples and violet light was selected. In total, 1132 photographs were in this entire study. Results indicated that photography with FLS was a viable non-destructive, chemical free and effective method for blood detection on dark fabrics. Furthermore, violet light with no filter was the most effective light source for viewing blood stains on dark fabrics without using chemicals. Using the violet light, washed fabric without detergent retain bloodstain for up to six cycles while fabric washed with detergent was only able to retain bloodstain in only two cycles